Descrição parasitológica, epidemiológica e hematológica do Galea spixii (Wangler, 1831) de vida livre no Estado da Paraíba - Brasil - Gomes, Carla Caroline Soares (2018)
The interaction between man, domestic animal and wildlife can cause and lead to the spread of many diseases, being infectious or parasitic agents, but little attention is given to the role of these diseases in conservation biology. Therefore, understanding the parasitic and infectious biodiversity of wildlife is of paramount importance in order to establish the role of these animals as reservoirs of pathogens and parasites. The present study aimed to test Mycoplasma sp., Babesia sp., Ehrlichia sp. and Bartonella sp. in wild mammals Galea spixii and to identify the natural parasites of this species, focusing on the importance of animals as potential reservoirs, as source of infection and its impacts Animals were captured in the immediate geographic region of Campina Grande, using Tomahawk-type traps, identification of rodents was made by the Rodents Guide of Brazil. The animals were anesthetized and euthanized with an overdose of the association of dissociative anesthetics after general anesthesia. The collection of the arthropods was done by the method of treatment, skin scrapings and swab of the auricular pavilion, after the collection were lightened with 10% potassium hydroxide and identified with a specific key. The coprological examination was performed with the Fill FLOTAC and mini-FLOTAC Kits. Blood collection was done by intracardiac puncture and the samples were sent to the Laboratory of Clinical Pathology of the Federal University of Paraíba - UFPB to perform the blood count and to the Laboratory of Zoonoses and Molecular Epidemiology and Laboratory of Diseases Transmitted by Vectors at the Federal University of Paraná - UFPR, for DNA extraction and infection of pathogens. No infections were detected for Mycoplasma sp., Babesia sp., Ehrlichia sp. and Bartonella sp. in G. spixii. The ectoparasites identified were: Gliricola quadrisetosa, Gyropus ovalis, Laelaps sp. and Chirodiscoides caviae. In the coprological examination were detected Nematode Eggs, Cestode Eggs and Coccidia Oocysts. The study of these pathogens in wild animals involves aspects of public health, animal and environment, so it is necessary to know the possible species that serve as reservoirs infectious and parasitic agents.